Patient based factors influencing drug compliance among hypertensive patients in a tertiary care hospital in Mysore - BM, Shrinivasa; Yadav, Kavita; MR, Narayana Murthy; HS, Kavitha (International Journal of Research in Medical Sciences, 2017)
Background: Hypertension is deemed as the tip of the iceberg due to the mortality and morbidity associated with it. A major factor accounting for inadequate treatment of hypertension is poor compliance. Methods: Morisky 8-Item Medication Adherence Questionnaire was used for a cross sectional study. The term compliance is defined as the extent to which the patient’s behaviour coincides with the clinical prescription, implying that the patient defaults by not following the advice of the health care provider Results: Mean age of the participants was 59.2yrs (S.D. 10.37 yrs). Compliance was found to be good 71.3% of respondents, medium in 20.4% and poor in 8.3%.52.8% had one or two other ailments (diabetes, asthma etc.). Conclusions: Patient’s medication compliance is a multifactor behaviour in which the role of patient’s attitude is very important. Patients related factors known to affect compliance were equally distributed among good, medium and poorly compliant participants